2012
DOI: 10.1186/1687-1499-2012-30
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable parasitic antennas for compact mobile terminals in multiuser wireless systems

Abstract: This article considers the exploitation of parasitic antenna arrays in multi-user (MU) wireless communication systems by using their adaptive beamforming capabilities in order to improve the average system throughput. The use of parasitic arrays and especially the electrically steerable passive array radiator (ESPAR) antennas enables the design of terminals with a single RF front-end and reduced antenna dimensions, i.e., lightweight and compact mobile terminals. Although the beamforming capabilities of active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Radio technology is based on Orthogonal Frequency Division Multiple Access (OFDMA) and it applies sophisticated scheduling and multiple antenna methods. The role of the antenna system performance is thus determinant, and as a result increasing interest is being given to novel multiple antenna schemes [2][3][4][5][6][7][8][9], to increase the Signal to Interference plus Noise Ratio (SINR) and the throughput performance.…”
Section: Imentioning
confidence: 99%
See 1 more Smart Citation
“…Radio technology is based on Orthogonal Frequency Division Multiple Access (OFDMA) and it applies sophisticated scheduling and multiple antenna methods. The role of the antenna system performance is thus determinant, and as a result increasing interest is being given to novel multiple antenna schemes [2][3][4][5][6][7][8][9], to increase the Signal to Interference plus Noise Ratio (SINR) and the throughput performance.…”
Section: Imentioning
confidence: 99%
“…Intelligent/smart antennas [2,3] (based on electronically reconfigurable arrays, either in switched beam mode or in adaptive phased array mode), space-time coding [4], vertical sectorization [6,7], or multiple antenna [3,[8][9][10] techniques have been proposed to increase the capacity gain in 3GPP LTE. As mentioned, LTE aims for simpler and lower-cost solutions.…”
Section: Imentioning
confidence: 99%
“…Then the authors in [9] demonstrated M orthonormal basis beam patterns to analyse aerial degree of freedom (aDOF) and efficient degree of freedom (eDOF). Later, the authors in [10] applied the beamspace MIMO with ESPAR antenna into multi-user MIMO scenario. The authors proposed channel estimator based on the basic beam patterns in [11].…”
Section: Introductionmentioning
confidence: 99%
“…Blind interference alignment was implemented utilizing the reconfigurability feature of the ESPAR antenna in [11]. Other applications of ESPAR antennas in multiuser systems can be found in [12].…”
Section: Introductionmentioning
confidence: 99%